2020
DOI: 10.1128/jvi.00949-20
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of PA-X Contributes to Virulence and Transmission of H3N8 and H3N2 Canine Influenza Viruses in Dogs

Abstract: Equine-origin H3N8 and avian-origin H3N2 canine influenza viruses (CIVs) prevalent in dogs are thought to pose a public health threat arising from intimate contact between dogs and humans. However, our understanding of CIV virulence is still limited. Influenza A virus PA-X is a fusion protein encoded in part by a +1 frameshifted open reading frame (X-ORF) in segment 3. The X-ORF can be translated in full-length (61-amino-acid) or truncated (41-amino-acid) form. Genetic analysis indicated that the X-ORFs of equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Recombinant viruses encoding the PA-X amino acid change R195K, showed decreased shutoff activity and showed increased replication and transmission in ferrets but not in chickens [ 60 ], suggesting that this amino acid change might have contributed to cross-species transmission of H7N9, H5N6, and H1N1/2009 viruses from animal reservoirs to humans [ 60 ]. In the case of canine IAV, genetic analysis indicated that within the PA-X, X-ORFs of equine-derived H3N8 and avian-derived H3N2 viruses encoded 61 amino acids but were truncated after introduction into dogs [ 61 ]. Truncation of PA-X suppressed expression from co-transfected plasmids in cells and enhanced viral pathogenicity and transmission in dogs, suggesting that truncation of PA-X might be important for the adaptation of influenza viruses to dogs [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant viruses encoding the PA-X amino acid change R195K, showed decreased shutoff activity and showed increased replication and transmission in ferrets but not in chickens [ 60 ], suggesting that this amino acid change might have contributed to cross-species transmission of H7N9, H5N6, and H1N1/2009 viruses from animal reservoirs to humans [ 60 ]. In the case of canine IAV, genetic analysis indicated that within the PA-X, X-ORFs of equine-derived H3N8 and avian-derived H3N2 viruses encoded 61 amino acids but were truncated after introduction into dogs [ 61 ]. Truncation of PA-X suppressed expression from co-transfected plasmids in cells and enhanced viral pathogenicity and transmission in dogs, suggesting that truncation of PA-X might be important for the adaptation of influenza viruses to dogs [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of canine IAV, genetic analysis indicated that within the PA-X, X-ORFs of equine-derived H3N8 and avian-derived H3N2 viruses encoded 61 amino acids but were truncated after introduction into dogs [ 61 ]. Truncation of PA-X suppressed expression from co-transfected plasmids in cells and enhanced viral pathogenicity and transmission in dogs, suggesting that truncation of PA-X might be important for the adaptation of influenza viruses to dogs [ 61 ]. Importantly, these results demonstrate an evolution in the abilities of NS1 and PA-X proteins to induce host shutoff and show how this is beneficial for IAV.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the human IAVs, including 1918 pandemic strains, encode a 252-amino-acid-length PA-X, with 61 C-terminal amino acids that result from the frameshift and are unique to PA-X [17]. Nevertheless, some IAVs, including the 2009 human pandemic H1N1 (pH1N1), canine and some swine influenza viruses encode a 232 amino acids-length PA-X because of an stop codon at position 42 of the X open reading frame (ORF) [10,18].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the human IAV, including 1918 pandemic strains, encode a 252 amino acid-length PA-X, with 61 C-terminal amino acids that result from the frameshift and are unique to PA-X [16]. Nevertheless, some IAVs, including the 2009 human pandemic H1N1 (pH1N1), canine and some swine influenza viruses encode a 232 amino acids-length PA-X because of an stop codon at position 42 of the X open reading frame (ORF) [9,17].…”
Section: Introductionmentioning
confidence: 99%